Role of Wireless Network and Technology for Development of Business Sector in Kathmandu Valley - Sunar, Abhishek (Nepalese Journal of Business, 2024)
This study examines the role of wireless network and technology for development of business sector in Kathmandu Valley. Business growth and development is the dependent variable. The selected independent variables are adoption and implementation of wireless technology, type of wireless technology used, level of investment, training and education, and market and industry trends. The primary source of data is used to assess the opinions of respondents regarding adoption and implementation of wireless technology, type of wireless technology used, level of investment, training and education, and market and industry trends. The study is based on primary data of 123 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of role of wireless network and technology for development of business sector in Kathmandu Valley. The study showed a positive impact of adoption and implementation of wireless technology on business growth and development. It indicates that high adoption and implementation of wireless technology, higher would be the level of business growth and development. Similarly, the study showed a positive impact of type of wireless technology used on business growth and development. It indicates that quality type of wireless technology to the customers leads to increase in business growth and development. Likewise, the study showed a positive impact of level of investment on business growth and development. It indicates that higher the level of investment in wireless technology, higher would be the level of business growth and development. Further, the study showed a positive impact of training and education on business growth and development. It indicates that positive perception on training and education leads to increase in business growth and development. Moreover, the study showed a positive impact of market and industry trends on business growth and development. It indicates that market and industrial trend in wireless technology adoption and usage leads to increase in the level of business growth and development.